Political chronicles from Mars. A reading of the Martian Chronicles, by Ray Bradbury, from political theory (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In this article we will indicate differences and significant questions for present political theory, such as mental violence and political fantasies; resistance; isegoria as a fundamental democratic notion; relations between knowledge, life and science; theoretical space travel; colonial encounters; or relations of alterity and political identity; all from the suggestions encoded in Ray Bradbury´s work, The Martian Chronicles. This is an attempt of theoretical enrichment for political philosophy from a literary text that takes us away from Earth.
Keywords: literature of science fiction; political-fiction; utopian societies